Digital Health/e-Health Literacy among University Students in the COVID-19 Era: A Systematic Review - Mohammad Sadegh Fallahi; Arezoo Faridzadeh; Mehrnaz Salahi; Reyhaneh Mehrabani; Hanieh Karimi; Ali Faraji; Saba Imanparvar; Masih Falahatian; Mohammadamin Bayat; Narges Norouzkhani; Seyed Amirhossein Mazhari; Minoo Roostaie; et al. (Journal of Medical Education and Curricular Development)
OBJECTIVE During the severe acute respiratory syndrome coronavirus 2 pandemic, could be observed an established use of online information in the field of coronavirus disease worldwide. As a systematic review study, the present investigation aimed to evaluate related studies about digital health/e-health literacy among university students in the coronavirus disease 2019 era. METHODS Three electronic bibliographic databases (PubMed/Medline, Scopus, and Google Scholar) were searched from 2020 until June 2022, and articles were screened according to pre-established inclusion criteria. RESULTS Fifteen studies were included in this systematic review study. All of the studies were cross-sectional in design, and in total, 45,255 students were evaluated. The majority of studies report health literacy scores among university students that are lower compared to reference samples. Students’ health literacy is influenced by different variables (age, gender, socioeconomic background, sources of online information, well-being, and satisfaction with data). CONCLUSION Digital health literacy (DHL) shapes health behaviors and actions. To enhance DHL, multidisciplinary teams from diverse fields can design curricula suitable for students. The internet’s role in DHL is crucial, but it can also spread misleading content. Therefore, professionals should provide clear, evidence-based information and encourage critical data evaluation. Future studies should use robust sampling methods, consider students with limited internet access, and address the unique needs of specific populations, such as those with disabilities and low socioeconomic status.